Aquaculture State, Challenges and Technologies in the Middle East - Shaima Ibrahim Alameri; Maitha Ahmed Almakhmari; Sathiya Maran; Reem Yousef Almansoori; Sabra Ahmed AlQubaisi; Aisha Abushelaibi; Kok Song Lai; Swee Hua Erin Lim (Turkish Journal of Agriculture: Food Science and Technology, 2021)
The aquaculture industry in the Middle East (ME) is still relatively new compared to other parts of the world, making this region highly dependent on other countries for the production of food and feed needs. Aquaculture activities in the world at current is mainly focused in China; this may be propelled by its own internal demand for seafood as determined by the United Nations Food and Agriculture Organization (FAO). Challenges faced in the ME has not been elucidated so far and the issues arising might be unique only to this region due to aquaculture being in the initial stages coupled with water access and limitations, climate and geography, in addition to pollution. This review paper will present and discuss global needs for seafood focusing later on the needs in the ME, followed by a discourse into the importance, types and challenges of aquaculture in the ME. Baseline knowledge and infrastructure to enhance knowledge is a pressing need at this stage of infancy. It is hope this sector will continue to develop, and with the support of stakeholders, aquaculture in the ME will achieve a state of independence.